Pendampingan Teknis Elevasi Struktur Dan Penerapan K3 Pada Pekerjaan Rehabilitasi Pondasi Tiang Ulin Sdn Balah Paikat Kabupaten Hulu Sungai Selatan - * Arifin; * Misnawati; Ahmad Riduan; Elva Shanty Widuri; Trie Rezky Novianti; Irsyandi Syifa Setiady; Hafiz Abdullah Nor Fajar (CV. SINAR HOWUHOWU, 2026)
This Community Service (PkM) activity aims to provide technical assistance for structural elevation and the implementation of Occupational Safety and Health (K3) in the rehabilitation work of ironwood pile foundations at SDN Balah Paikat, Hulu Sungai Selatan Regency. The school building stands on swampy land with a low floor elevation so that it often experiences flooding during the rainy season, while the previous building lifting process was carried out manually without adequate elevation control and K3 procedures. The activity was carried out through a participatory approach that included preparation and coordination stages, observation and initial elevation measurements, technical assistance for the lifting process (jacking) in stages and simultaneously using simple measuring tools, the implementation of K3 through socialization and the use of personal protective equipment (PPE), as well as evaluation and provision of technical recommendations. The results of the activity showed that the building lifting process became more controlled, the elevation between columns was more uniform, and the distribution of structural loads was more stable. In addition, worker awareness of the implementation of K3 during the work also increased. This activity has an impact on reducing the potential for waterlogging, increasing the safety and comfort of the building, and creating a safer and more usable learning environment.